(untitled) (International Journal of Veterinary Medicine and Animal Science, 2025)
Good quality feed has been a major challenge in livestock production in the tropics, especially during the dry season, which is characterized by low-quality forages. Good nutrition is important because it is associated with improving the performance, health, reproduction and productivity of animals. This study aimed to evaluate the growth performance and digestibility of Red Sokoto goats fed Jatropha curcas kernel cake treated with Pseudomonas aeruginosa. Twenty Red Sokoto goats with average weight of 8.20±1.1kg were completely randomized into diets A (control: 0% Jatropha curcas kernel cake), B (10% Pseudomonas treated Jatropha curcas kernel cake), C (15% Pseudomonas treated Jatropha curcas kernel cake), and D (20% Pseudomonas a treated Jatropha curcas kernel cake). Jatropha curcas kernel cake was used as a replacement for groundnut cake over a 70-day experimental period. Data was analyzed as one-way ANOVA in SAS and means were separated with Duncan multiple range test at alpha of 5%. There was significant variation in the crude protein, ether extract and crude fiber of the experimental diets. A significant (p<0.05) difference was observed in the dry matter intake of the animals with values of 433.48g, 426.46g, 339.29g and 328.78gfor diets A, B, C and D respectively. Dry matter intake was significantly lower (p<0.05) for animals fed diets C and D. The crude protein (12.02-15.85%), crude fiber (5.88-8.76%) and gross energy (376.97-388.43Kcal/100g) contents were adequate for animals of such age. The nutrient digestibility was significantly (p<0.05) higher in diets supplemented with treated jatropha kernel cake. There was no significant difference in the weight gain of the animals on diets A, B and C, however, animals fed diet D had significantly (p<0.05) lower weight gain and average daily gain. It was concluded that treatment of Jatropha curcas cake with Pseudomonas aeruginosa was effective in detoxifying Jatropha curcas kernel cake as it has no deleterious effect on growth performance and improved nutrient digestibility of the experimental animals.